(3CQLhRI aj GdejbGJ hGdgjFI hGdJfLjes - (3CHh GdMSf Ydj Hf CHj Ydj GdbSfWjfjs
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdaGWQ GdeGdc Gdedc GdYdi GdbGOQ eRjf GdCadGc HGdchGcH djgJOi HWGdY hZGQH s
(3BNQgG (B:s
(3hGONd HYQV GdHOQ ZjQ hGf ai GdLOhd GdehVhY ddCdhGf JHUQ dhf Pdc GdNSha eMbbkG ef ZjQ eG JMQja Je GdQLR GdeHGQc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(909(2)) s
Keywords: (3Gdadcs